The relationship between the use of multiple methods in promoting muscle recovery and certain physiological variables after high-intensity physical exertion in young basketball players - Abs, L.Dr. Fadhil Muhammad; Khudair, Asst.Prof.Dr. Mustafa Fadel (Sulaimani Journal for Humanities, 2045)
Because athletes, especially basketball players, engage in high-level competitions during the training season, with long durations of matches and extended training periods to develop their skills and improve their abilities, which requires proper adaptation and adjustment of the athlete's various bodily systems and organs, all of this puts stress on their bodies and their mental state. Furthermore, prolonged training can lead to decreased activity in various energy systems and negatively impact the condition of different bodily systems. Therefore, it is essential to focus on the principle of balancing and regulating training loads according to scientific principles and field studies, and to optimally utilize muscle recovery methods. This is the introduction to the research and its importance. In order to elevate the athlete's physical, psychological, and intellectual level, optimal use of muscle recovery methods is crucial. Among the most important methods employed in the sports world and used by dedicated coaches is focusing on concluding training sessions with: (Various jogging exercises – static stretching exercises) and mental relaxation sessions, as well as consuming nutritional supplements rich in elements that aid and accelerate muscle recovery processes, given their positive effect on reducing training burdens. The research problem can be summarized as follows: In finding and trying different methods that raise the athlete’s state of balance and restore his functional systems to a stable state that enables him to practice his normal life and return to subsequent training units in a balanced physical and mental state, ready to bear the burdens of training and competition. The research objectives came to identify the superiority of mental relaxation techniques over the method of calming (varied jogging - static stretching exercises) and taking magnesium and curcumin supplements in accelerating the muscle recovery process.
Keywords: Mental relaxation; muscle stretching; effects of athletic training; highintensity training; curcumin supplement; magnesium supplement